Ecological Restoration for Achieving the Goals of Land Degradation Neutrality with Special Reference to India - Dagar, Jagdish Chander; Gupta, Sharda Rani (Journal of Soil Salinity and Water Quality, 2022)
Land degradation due to deforestation and poor agricultural practices is among one the major global challenges to meeting the food requirement of an ever-increasing population. Up to 40% of the land is degraded globally impacting 50% of humanity and costing the global economy around 10 percent of the gross productivity. The Land Degradation Neutrality (LDN), which emerged from the 2012 UN Conference on Sustainable Development, commits countries to “strive to achieve a land degradation-neutral world” by the year 2030. The IUCN report has analyzed the drivers and pressures of land degradation using the Drivers-Pressure-State-Impact-Response (DPSIR) model in which the root causes of land degradation are termed “Drivers”, whereas the direct causes are termed “Pressures”. The “Drivers” or underlying causes of land degradation include those due to natural causes, conditions, and biophysical processes, such as intrinsic land quality, climatic variables, and soil biodiversity; and others related to human society, such as poverty, demographic change, and economic, and political factors. Whereas proximate Pressures include faulty methods of agriculture, deforestation, desertification, and infrastructure developments. Several long-term field experiments carried out during the last 3-4 decades across the globe have shown that integrating trees with forage grasses, arable crops, and under-explored crops (including high-value aromatic and medicinal plants) using appropriate technologies can contribute to a significant improvement in sustainable agricultural production, as well as meeting the challenges of land neutrality, and mitigating the climate change. Devising sustainable strategies for restoring degraded land at the local, national, regional, and global levels is imperative for the timely realization of the UN SDGs. The UN Decade for Ecosystem provides opportunities for restoring degraded land for the benefit of both people and the planet. However, individuals, policymakers, and institutions must come forward to make use of this opportunity to restore the health of degraded lands for a sustainable future.